Adapting the Current Opioid Misuse Measure (COMM) for people with chronic pain and disability due to arthritis: The development of the COMM 11-PWDA. Issue 2 (June 2022) - Mallery Lankford, Coretta; Paez, Kathryn; Yang, Manxi; Lin, Amy
Abstract: Background: People with arthritis, a leading cause of disability, may be prescribed long-term opioid therapy to manage chronic pain. Regular use of opioids can increase risk of overdose and opioid use disorder (OUD). Objective: The purpose of our research was to validate an instrument to screen for harmful opioid use in people with disability and chronic pain due to arthritis (PWDA). Methods: We tested the Current Opioid Misuse 1 Measure (COMM), an instrument designed for monitoring people with chronic pain on long-term opioids, with 318 PWDA who are taking long term opioids from February–June 2020. We validated the COMM against a Diagnostic and Statistical Manual for Mental Health Disorders, 5th edition (DSM-V) assessment instrument and risk factors for OUD. Final item selection was based on advisory group input, cognitive testing, and empirical evaluation of items. We calculated a cutoff score using receiver operating characteristic (ROC) analysis. Results: Of the 17 items on the original COMM, we found that 11 items measured the intended construct–opioid use in a way that causes harm in PWDA. Once limiting the instrument to these 11 items (The COMM 11-PWDA), the items had excellent internal consistency and validity with the DSM-V measure. Reasonable sensitivity and specificity were established. Conclusions: The COMM 11-PWDA is a valid instrument for screening for and monitoring harmful opioid use in PWDA.